Disrupting together: the challenges (and opportunities) for platform co-operatives (London, 2018)
"Platforms – like Uber, Deliveroo, or TaskRabbit – connect services and products with consumers. With both sides theoretically having control over the interaction, and investing in the platform to reap the rewards, the rapid spread of platforms has the potential to revolutionise capitalism. But increasing concerns over the past few years around tech monopolies and the potential erosion of workers’ rights through the gig economy have raised questions over who really holds control over the platforms, and what impact this has on workers and customers."